2022
DOI: 10.3390/ijms23031630
|View full text |Cite
|
Sign up to set email alerts
|

Docking and Molecular Dynamic of Microalgae Compounds as Potential Inhibitors of Beta-Lactamase

Abstract: Bacterial resistance is responsible for a wide variety of health problems, both in children and adults. The persistence of symptoms and infections are mainly treated with β-lactam antibiotics. The increasing resistance to those antibiotics by bacterial pathogens generated the emergence of extended-spectrum β-lactamases (ESBLs), an actual public health problem. This is due to rapid mutations of bacteria when exposed to antibiotics. In this case, β-lactamases are enzymes used by bacteria to hydrolyze the beta-la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…During the production phase, each system was run for a total of 10 ns. The final 2 ns of these simulations were utilized for the MMPBSA calculations, consistent with methodologies utilized in previous work [109,110]. This comprehensive approach helps to ensure a robust exploration of the system's phase space.…”
Section: Molecular Dynamics Configurationmentioning
confidence: 99%
“…During the production phase, each system was run for a total of 10 ns. The final 2 ns of these simulations were utilized for the MMPBSA calculations, consistent with methodologies utilized in previous work [109,110]. This comprehensive approach helps to ensure a robust exploration of the system's phase space.…”
Section: Molecular Dynamics Configurationmentioning
confidence: 99%
“…These techniques can anticipate the binding affinity, molecular interactions, and physiochemical characteristics of the hit compounds, saving time and money [32]. Previously, a number of in silico studies have been conducted using molecular docking and molecular dynamics simulations for the discovery of potent inhibitors of β-lactamases, particularly NDM-1, from various natural resources [34][35][36][37]. These studies have identified many phytochemicals with different chemical structures and properties that can inhibit NDM-1 [38,39], but none of them have yet been approved for use in humans.…”
Section: Introductionmentioning
confidence: 99%
“…oil of B. vulgaris leaves and β-lactamase. A: sulfur pentafluoride; B: squalene; C: 3-aminodibenzofuran; D: 2-monolaurin; E: clavulanic acid (native) 26. Moreover, the molecular docking of eight L2-β-lactamase inhibitors shows that these compounds possess ∆G values (lowest to the highest) as follows: relebactam -6.8 kcal/ mol, meropenem -6.54 kcal/mol, nitrocefin -6.28 kcal/ mol, avibactam -6.14 kcal/mol, imipenem -5.34 kcal/mol, carbapenem -5.24 kcal/mol, ceftazidime -4.83 kcal/mol, and aztreonam -4.6 kcal/mol, respectively 27.…”
mentioning
confidence: 99%